(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This article assessed the proximate, microbiological and sensory properties of aquaculture and wild catfish smoked with selected word biomass. The samples were smoked using wood chunks then analyzed for its proximate, microbiological quality and sensory attributes of the samples. Thirty (30) semi-train panelist were employed, Hedonic scale ranging from (9) means like extremely to one (1) meaning dislike extremely were used and the data obtained were analyzed using Minitab version 17 statistically for mean and standard deviation. The result of proximate composition in table 1, showed that there were significant difference among the samples, where moisture ranged from (10.07 – 14.61%), ash (3.37 – 4.01%), fat (19.61 – 20.61%), fibre (0.51 – 0.82 5%), protein (48.11 – 55.3%) and carbohydrate content ranged from (9.57 – 16.05%). Table 2, presents the results of microbial quality were the total viable bacterial count ranged from (1.22x103 – 7.33x103 cfu/g) and total fungal counts ranged from (1.00x103 - 4.33x103 cfu/g). The sensory evaluation of smoked catfish samples presented in table 3. Showed that appearance ranged from (7.73 - 8.95) followed by flavour attributes with mean score value ranged from (7.73 - 8.20), taste (7.63 - 8.365), aroma (7.66 - 8.23), mouth feel (7.70 - 8.30) and the overall acceptability ranged from (7.53 - 8.43). This article revealed that wood biomass obtained from selected woods could be effective in improving the organoleptic properties of smoked catfish, extends shelf-life without significant changes on the proximate composition.